Psychological Abuse of Individuals with Down Syndrome and its Social Impact on Mothers (Comprehensive Journal of Science, 2026)
This study examined the impact of psychological abuse directed at children with intellectual disabilities (Down syndrome) on mothers’ social well-being. A descriptive-analytical approach was used on a sample of 40 mothers through a questionnaire analyzed using SPSS. Results indicated that the level of psychological abuse was very low, while the social impact on mothers was moderate. A significant correlation was found between psychological abuse and certain aspects of social interaction and stigma. No statistically significant differences were found due to demographic variables.
Keywords: Psychological abuse, Down syndrome, intellectual disability, social impact, mothers, social support